Anterior vaginal wall protrusion in pregnancy: a case report. Issue 1 (January 2020) - Lu, Dajiang; Liu, Fang; Ning, Xue; Zhang, Hua; Huang, Yan
Vaginal prolapse rarely complicates pregnancy. We experienced a 36-year-old, gravida 3, para 1 woman who presented at 37 weeks' gestation with gestational diabetes mellitus and a large anterior vaginal prolapse that could not be reduced manually or by bed rest. After obtaining consent, a cesarean section was successfully performed, and a live neonate delivered. The prolapsed anterior vagina recovered spontaneously following the cesarean operation. A vaginal prolapse in pregnancy is rare. Elective or emergency cesarean section is a possible treatment option when the prolapse cannot be reduced manually or by bed rest. Our case highlights the importance of routine obstetric examinations for early detection of a vaginal wall prolapse.